Resources and Suggestions to Support Black Women’s Maternal Health - Tyler S. Nesbit; Karen Awura-Adjoa Ronke Coker; Sarah McKune; Larry Forthun; LaToya O'Neal (EDIS)
This publication is intended to support Black women in navigating the healthcare system before, during, and after pregnancy. Written by Tyler S. Nesbit, Karen Awura-Adjoa Ronke Coker, Sarah McKune, Larry Forthun, and LaToya O’Neal, and published by the UF/IFAS Department of Family, Youth and Community Sciences, November 2022.